Variation of lumber properties in genetically improved full-sib families of Douglas-fir in British Columbia, Canada. (28th March 2018) - Filipescu, Cosmin N; Stoehr, Michael U; Pigott, Don R
Abstract: Tree breeding to increase forest productivity and resilience is an active area of research. Many studies have examined wood traits of interest to lumber manufacturing, such as wood density, knottiness and microfibril angle, due to the generally negative correlation between rate of growth and wood quality. Relatively little is known, however, about the variation in structural parameters of lumber, i.e. modulus of elasticity (MoE) and modulus of rupture (MoR), in genetically improved trees. In this study we evaluate physico-mechanical properties of lumber from 12 full-sib families in a first-generation Douglas-fir progeny trial. Trees were harvested at age 33 and milled into boards that were tested for MoE and MoR, with specific gravity (SG) and acoustic velocity (AV) also measured. Results indicate that families with lower growth tend to perform better for MoE and MoR, although there are certain families that exhibit higher growth and better MoE and MoR. Boards with less juvenile wood had higher MoE and MoR indicating the significance of board orientation due to sawing pattern; this suggests that radial variation of wood properties is an important factor for genetically improved families. Overall, AV was a better predictor than SG for both MoE and MoR, indicating the potential of using AV in future tree breeding, as well as for product segregation. Findings from this study provide evidence to further develop breeding programmes of Douglas-fir in order to optimize wood production, product quality and ultimately value recovery.